Pengaruh Sistem Informasi Pada Jasa Pengiriman Barang - Ridwan Izza Aditya; Aryanto Nur; Finar Al Khori; Halby Stifandri (Journal Of Informatics And Busisnes, 2024)
This study analyzes the impact of information systems on J&T Express delivery services, with a focus on service quality and customer satisfaction. The survey involving 95 respondents showed that key elements such as reliability, responsiveness, assurance, and empathy have a significant influence on customer satisfaction and loyalty. J&T Express is known for its timely delivery and quick response, supported by an information system that allows real-time tracking of shipment status, so that customers feel more comfortable and informed. Competitive prices for domestic shipping are also one of the main factors attracting customers, although there are some complaints about the high cost of international shipping. Transparency in pricing has also increased customer trust in J&T Express services. In addition, the flexibility of services such as the option of picking up goods from home or office and 24-hour operating hours provides greater convenience, especially for customers with busy schedules. However, several obstacles, such as internet network instability and delivery delays, are still challenges that need to be addressed immediately so as not to negatively affect customer satisfaction and loyalty. The results of this study emphasize the importance of continuous improvement in service quality as well as information systems to maintain J&T Express's competitiveness in the highly competitive delivery services industry.